A Study on Listing Day Price Performance of BSE SME IPOs and its Determinants - Singh, Amit Kumar; Anand, Ashween (Indian Journal of Finance, 2020)
SME exchange is a relatively new platform of raising equity finance in India. A lot of research has been done on IPOs, but there is a dearth of literature on SME IPOs in India. This paper aimed to fill this research gap, to some extent, by addressing the following questions : What is the listing day price performance of BSE SME IPOs ? Are BSE SME IPOs underpriced or overpriced ? What are the factors that determine the BSE SME IPO returns on the listing day ? The study focused on a sample of 176 BSE SME listed IPOs of equity shares issued by small and medium enterprises during the period from February 23, 2012 – March 31, 2017. The results showed that on an average, SME IPOs provided positive returns of 8.66% on the listing day. Age, subscription, issue price, listing delay, market sentiment, and financial & construction sector dummies had a significant impact on listing day price performance of SME IPOs. An important implication of the study is that it supports SEBI’s initiatives to reduce the issue listing time.